Capitalismo baseado em dados e a proteção do trabalhador: investigações para uma utilização coletiva de ferramentas de proteção de dados dos trabalhadores no Brasil - Eugênio Delmaestro Corassa (2022)
This dissertation aims to understand how the phenomenon of data capitalism interacts with labor relations, demonstrating the viability of Law no. 13.709/18 (LGPD) as a regulation tool, as well as demonstrating whether the collective construction of data protection is possible with the use of collective protection mechanisms of the Brazilian legislation, including union action. To this end, this dissertation analyzes the reality of data capitalism, as a phenomenon associated with big data and with an ever-increasing extraction and processing of data, which is often personal data. In this way, this new phenomenon impacts workers because it promotes the continuous replacement of managerial functions, associated with the elements of direction, discipline, and punishment, by automated decision making or data-driven decision making systems. In this sense, this thesis will analyze how the protection of personal data, especially in the figure of the LGPD, proposes to deal with the issue. This will be done, also, by analyzing the limitations of the LGPD in the face of the complex problems presented by data capitalism, as well as the problems of the law to deal with the reality of workers in Brazil. Thus, as a solution, we will consider the possibility of collective action for the protection of workers' data in Brazil, from the analysis of the possibility of collective action, through trade unions, for the regulation and control of algorithmic management processes, as well as through multisectoralism and collective action, in the form of public civil action. We seek, in this sense, to identify possible mechanisms to correct asymmetries between employees and employers with regard to data protection.